Elevated temperature and waterlogging decrease cottonseed quality by altering the accumulation and distribution of carbohydrates, oil and protein. Issue 1 (7th October 2020) - Xu, Bingjie; Chen, Yinglong; Wang, Haimiao; Zhao, Wenqing; Zhou, Zhiguo
Abstract : Soil waterlogging and high‐temperature events have occurred simultaneously in recent years in the Yangtze River basin cotton belt region of China, negatively affecting the development and quality of cottonseed. This study investigated the effects of the combination of elevated temperature (ET) (34.1/29.0°C) and waterlogging (3 or 6 days) on the accumulation and distribution of oil, protein and carbohydrates in cottonseed during flowering and boll development. The results showed that ET resulted in greater decreases in cottonseed biomass under waterlogging than under control conditions. The combination of waterlogging and ET significantly limited the accumulation of carbohydrates and oil contents. However, ET promoted protein accumulation and compensated for the negative effects of 3‐day waterlogging on the final protein content. The combined ET and 6‐day waterlogging significantly decreased the final contents of oil and protein by limiting carbon flux and NADPH supply because of the decreased activities of phosphoenolpyruvate carboxylase (PEPC, EC 4.1.1.31) and glucose‐6‐phosphate dehydrogenase (G6PDH, EC 1.1.1.49). The PEPC activity was correlated more with protein content than oil content. In addition, simultaneous exposure to waterlogging and ET resulted in lower unsaturated fatty acid/saturated fatty acid ratios and essential amino acid/non‐essential amino acid ratios than did exposure to the individual factors alone. These findings could provide the theoretical support for the prospective assessment of effects of high temperature and waterlogging stresses on cotton production under climate change, and they can help to develop effective techniques in cotton cultivation.